2008
DOI: 10.1103/physrevb.77.134206
|View full text |Cite
|
Sign up to set email alerts
|

Short-range order and precipitation in Fe-rich Fe-Cr alloys: Atomistic off-lattice Monte Carlo simulations

Abstract: Short-range order (SRO) in Fe-rich Fe-Cr alloys is investigated by means of atomistic off-lattice Monte Carlo simulations in the semi-grand canonical ensemble using classical interatomic potentials. The SRO parameter defined by Cowley [Phys. Rev. B 77, 669 (1950)] is used to quantify the degree of ordering. In agreement with experiments a strong ordering tendency in the Cr distribution at low Cr concentrations ( 5%) is observed, as manifested in negative values of the SRO parameters. For intermediate Cr concen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
54
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 25 publications
13
54
0
2
Order By: Relevance
“…Upon heating the alloys decompose into Ferich and Cr-rich phases. The degree of the decomposition, hence the actual distribution of atoms (and values of the SRO-parameters) depends on samples' metallurgical histories as experimentally revealed in this study, and theoretically demonstrated by performing Monte Carlo atomistic simulations 18 .…”
mentioning
confidence: 94%
“…Upon heating the alloys decompose into Ferich and Cr-rich phases. The degree of the decomposition, hence the actual distribution of atoms (and values of the SRO-parameters) depends on samples' metallurgical histories as experimentally revealed in this study, and theoretically demonstrated by performing Monte Carlo atomistic simulations 18 .…”
mentioning
confidence: 94%
“…In contrast, the clustering energy for the CDMpot is positive for all reported cluster sizes and with a positive slope. Despite the poor agreement of the latter with DFT data, we note, however, that all potentials have been successfully applied in studies regarding Cr precipitation and short-range order [37][38][39][40]. The Cr-Cr repulsion resulting from DFT and the different potentials are compared in figure 6.…”
Section: Defect-free Fecrmentioning
confidence: 99%
“…can be found in Ref. 13, where we used a preliminary version of the present algorithm to study short-range order in FeCr alloys as a function of temperature and composition.…”
Section: A Sampling Structural Relaxation and Vibrationsmentioning
confidence: 99%
“…In the next section, we consider the precipitation of Cu in Fe-rich Fe-Cu nanocrystals as an illustration for the type of problems that can be studied using our algorithm. Other examples include the study of grain boundary pinning in Cu due to Fe impurities 11 , structural phase transformations of Cu precipitates in BCC iron 12 , short-range order in Fe-Cr alloys, 13 and the properties of helium bubbles in Fe and Fe-Cr alloys 14 . can be found in Ref.…”
Section: A Sampling Structural Relaxation and Vibrationsmentioning
confidence: 99%